Population affinities in pre‐colonial West Africa: The case of the burial cave Iroungou (Gabon, 14th–15th century CE) - (:unkn) unknown (My University, 2024)
Introduction: Our knowledge of the populations of sub-Saharan Africa in the periods before European colonization is limited. Few archeological sites containing human remains have been identified, and written sources for these periods are rare. The discovery in 2018 of the Iroungou sepulchral cave (Gabon), whose use predates the arrival of the Portuguese (14th–15th centuries CE), is an exceptional source of information: at least 28 individuals associated with numerous metal artifacts were found there. The anthropobiological remains were left in situ, but the eight best preserved crania were digitized.Objectives: This study focuses on the population affinities of these crania, whose morphology was described using 237 landmarks.Materials and Methods: Geometric morphometric analyses were used to compare the eight Iroungou specimens with 154 individuals representing 12 well-defined African populations. After alignment (Generalized Procrustes Analysis), morphological affinity was assessed using Euclidean and Mahalanobis distances, and posterior probabilities of population membership (discriminant analysis).Results: Results indicate that the eight Iroungou crania have, on average, more affinity with Bayaka Pygmy, followed by Central African Bantu. Nevertheless, individually, the Iroungou specimens show an important morphological variation and the eight crania can be separated into different affinity groups: Bayaka and Central African Bantu, KhoeSan, and East-African Bantu. Finally, one individual presents strong affinity with Somalis.Conclusion: This phenetic mapping of the Iroungou sample raises questions about the profile of the individuals deposited in the cave in a geographical area known for the Loango pre-colonial kingdom, which ruling class seemed to have had privileged relationships with the Pygmy populations.
Keywords: African Research